2-mercaptobenzimidazole inhibits corrosion and prolongs the lifetime of an epoxy resin coating on a copper-62 alloy surface in a simulated marine environment at 40 °C - Chen, Jingkang; Li, Xu; Xiao, Xujie; Zhu, Chengfei (Journal of vacuum science & technology. A, Vacuum, surfaces, and films, 2024)
Epoxy coatings are widely used on metal surfaces in marine environments, but are subject to corrosion. How to improve the corrosion resistance of such materials has therefore become an important research topic. In this study, the corrosion inhibitor 2-mercaptobenzimidazole (MBI) was added to the organic coating of the epoxy resin on the surface of the copper-62 alloy to extend the service life of the coating in marine environments. The corrosion inhibition efficiency of MBI for the copper-62 alloy in simulated marine environments was investigated by means of immersion corrosion tests, Tafel polarization tests, and electrochemical impedance spectroscopy (EIS). The effects of MBI on the damage process and water transport of epoxy coatings were also studied by EIS. It has been shown that MBI acts as an adsorption corrosion inhibitor by electro-attractively adsorbing on the surface of a copper substrate. For a total mass fraction of 0.5 wt. %, the corrosion inhibition efficiency was more than 90%, and the corrosion current density of the copper-62 alloy in simulated seawater with MBI was 6.01 × 10−7 A cm−2. The corrosion current density of the copper-62 alloy in simulated seawater is 1.382 × 10−5 A cm−2. When MBI was added to the epoxy organic coating at a ratio of 0.5 wt. %, the diffusion coefficient of the coating was as low as 9.72 × 10−11 cm2 s−1, and the time to failure of the coating was extended to 1656h, compared to the epoxy coating without the corrosion inhibitor. It has been demonstrated that the addition of MBI can increase the service life of copper-62 alloy/epoxy coatings in marine environments effectively.